Maternal obesity and gestational weight gain are modestly associated with umbilical cord DNA methylation. (September 2017) - Thakali, Keshari M.; Faske, Jennifer B.; Ishwar, Arjun; Alfaro, Maria P.; Cleves, Mario A.; Badger, Thomas M.; Andres, Aline; Shankar, Kartik
Abstract: Introduction: Maternal obesity (OB) and excessive gestational weight gain (GWG) are strong independent contributors that augment obesity risk in offspring. However, direct evidence of epigenetic changes associated with maternal habitus remains sparse. Methods: We utilized Bisulfite Amplicon Sequencing (BSAS) to conduct targeted DNA methylation association analysis of maternal obesity and excessive GWG with DNA methylation of select metabolism-related and imprinted genes. Umbilical cord (UC) tissue from infants born to normal weight and overweight/obese women from the Glowing study were utilized (n = 78). Results: In multivariable linear regression adjusted for relevant confounders, Institute on Medicine (IOM) GWG category and infant sex were significantly associated with UC IGFBP1 methylation, while gestation length was significantly associated with UC PRKAA1 methylation. In addition, infant fat mass (%) at 2 weeks of age was significantly associated with umbilical cord methylation of RAPTOR . While regression tree analysis confirmed findings from multivariable models demonstrating that maternal early pregnancy BMI and IOM GWG category are associated with fetal UC DNA methylation patterns for select metabolic and imprinted genes, in general, effect sizes were quite small and statistical significance was not maintained when accounting for multiple testing. Discussion: Our findings suggest that maternal obesity and excessive GWG are weakly correlated with offspring DNA methylation patterns at birth. Highlights: Examined maternal and infant variables associated with cord DNA methylation. Used multiple linear regression and recursive partitioning via regression trees. Maternal early pregnancy BMI was modestly associated with methylation of H19. Gestation length was weakly associated with PRKAA1 methylation. Infant fat mass significantly correlated with methylation of RAPTOR.